Technologies for Improving Professional Methodological Training of Future Music Teachers (Eurasian Journal of Learning and Academic Teaching, 2022)
This article talks about the technologies for improving the professional methodical training of the future music teacher. The article is devoted to the actual problem of contemporary art education to improve the professional training of future music art teachers for children’s inclusive education. Its purpose is to present the results of theoretical understanding of the developmental and healing potential of music, to develop technological support in future music art teachers professional training for children’s inclusive education